The spatial legacy of Australian mercury contamination in the sediment of the Molonglo River - Dylan Stinton; Larissa Schneider; Sara Beavis; Janelle Stevenson; William A Maher; Olha Furman; Simon Haberle; Atun Zawadzki (Elementa: Science of the Anthropocene, 2020)
Mercury (Hg) contamination is an environmental concern as a by-product of legacy mining in Australia. Here we investigate the spatial and temporal distribution of Hg in the Molonglo River system in New South Wales, Australia, and assess the physical and chemical factors influencing that distribution. Mercury concentrations in sediment cores were measured in conjunction with 210Pb and 137Cs dating to establish historical contamination. This was done at the source mine site of Captains Flat, New South Wales, and the system’s sink in Lake Burley Griffin, Australian Capital Territory. Additionally, surficial sediment Hg concentrations along the Molonglo River were analyzed to determine the spatial distribution of Hg. Analytical results showed the primary physical and chemical factors influencing Hg dispersion to be distance, total organic matter, and the presence of iron oxides and oxyhydroxides. The highest Hg concentrations were near the mine site at Captains Flat and decreased significantly with distance. Sediment core analyses in both Captains Flat and the lake showed reductions in Hg concentrations toward surficial sediment layers. It is suggested government-funded rehabilitation programs are playing a part in reducing the release of metal contamination.